Analysis of automation of bulk packaging line at Wixon Inc. - Putnam, Eric (Kansas State University, 2016)
The purpose of this thesis is to analyze the impact the installation of an automated packaging system would have on the predominately manual bulk packaging work centers at Wixon Inc., a privately held, integrated food and beverage developer, manufacturer, and processor. The objective of this thesis is to determine if converting to an automated system would minimize costs and increase line speeds. The owners desire a 3-year payback on the investment. In addition to the financial and economical aspects of automating the equipment, there are potential food safety and personnel safety improvements that would be brought to the firm by changing equipment. The firm’s owners want to be proactive and minimize any impact a reduction in the labor pool might see cause from the exit of workers from the Baby Boomer generation. Methods used to determine the objectives of this thesis include a comparative time study of bag filling rates, an analysis of incremental cost savings, net present value (NPV) analysis and return on investment (ROI). Data were collected from studies conducted by the engineering consulting firm of Middough Incorporated, from Wixon Inc. accounting records and, interviews of key Wixon employees. The report provided by Middough determined that the new system would be able to replace three work centers in the Bulk Packaging department based on bag fill rates and flexibility in bag sizes. This reduces the employee cost per bag. The incremental costs were analyzed using accounting records for past history. Floor space, labor costs and other integral costs were compared to determine what costsavings there may be. Cost savings were treated as cash flow. The NPV and ROI for the project used this cash flow to determine if an investment in automation is a wise one. The conclusion based on the analysis made was that, based on NPV the investment would be profitable. However, the 3-year payback of $1.5 million would not be possible under current assumptions. The automation would reduce the number of needed employees enough to absorb any reduction in the labor pool while providing increased food and employee safety.
Keywords: Spice mixing; Net present value; Payback method; Mechanized packaging